2021
DOI: 10.1038/s41598-021-98843-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary phenotype of individuals with chronic intestinal disorders

Abstract: Despite the known functional relationship between the gut and the liver, the clinical consequences of this circuit remain unclear. We assessed the hepatobiliary phenotype of cohorts with celiac disease (CeD), Crohn´s disease (CD) and ulcerative colitis (UC). Baseline liver function tests and the frequency of hepatobiliary diseases were analyzed in 2377 CeD, 1738 CD, 3684 UC subjects and 488,941 controls from the population-based UK Biobank cohort. In this cohort study associations were adjusted for age, sex, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In the literature, the prevalence of NAFLD in patients with IBD is variable. Two recent meta-analyses reported a pooled prevalence of NAFLD in IBD of 27.5%[ 75 ] and 32%[ 76 ]; older age, obesity, type 2 diabetes, longer IBD duration and previous surgery were the main risk factors associated with the development of NAFLD[ 77 ]. A further meta-analysis specifically addressing the role of IBD treatment on the risk of NAFLD found no significant association between medications of all types ( i.e.…”
Section: Non-immune-mediated Disordersmentioning
confidence: 99%
“…In the literature, the prevalence of NAFLD in patients with IBD is variable. Two recent meta-analyses reported a pooled prevalence of NAFLD in IBD of 27.5%[ 75 ] and 32%[ 76 ]; older age, obesity, type 2 diabetes, longer IBD duration and previous surgery were the main risk factors associated with the development of NAFLD[ 77 ]. A further meta-analysis specifically addressing the role of IBD treatment on the risk of NAFLD found no significant association between medications of all types ( i.e.…”
Section: Non-immune-mediated Disordersmentioning
confidence: 99%
“…Among 2377 individuals with CD, 6.1% received a diagnosis of cholelithiasis, which was significantly higher than controls (3.9%, p < 0.001); only 1.1% were diagnosed with unspecified cholecystitis. This value was greater than that observed in controls (0.7%), but the difference did not reach the statistical significance ( p = 0.071) [ 68 ]. Therefore, although one may speculate that gallbladder dysfunction may contribute to some dyspeptic complaints in CD patients, there are no clinical studies investigating this specific aspect, and no final conclusion can be made in this regard.…”
Section: Is There Any Clinical Implication Of Gallbladder Dysfunction...mentioning
confidence: 77%
“…A recent study found that among 3,684 UC patients, the prevalence of AIH was 0.24% ( 5 ). Patients with IBD had a higher prevalence of AIH, with odds ratios of 7.8 and 17.9 for men and women, respectively ( 5 ). These patients are more likely to fail treatment and develop cirrhosis ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging features of the bile duct resemble PSC while the clinical, biochemical, and histological features are consistent with AIH ( 3 ). The incidence of IBD is as high as 40–50% in PSC-AIH overlap syndrome patients ( 4 ); however, PSC-AIH overlap syndrome is rare in IBD patients ( 5 ). Herein, we described a 38-year-old male UC patient, who received a diagnosis of PBC after 2 years because of abnormal liver function.…”
Section: Introductionmentioning
confidence: 99%